Assemblages of certain benthic molluscs along the southwestern Atlantic: From subtidal to deep sea - Teso, Silvia Valeria (2019)
Background: We analyse the distribution of Gastropods and Chitons from shallow to deep waters along the southwestern Atlantic Ocean off Argentina and discuss possible factors determining the observed biogeographic patterns. Results: Three major biogeographic groups are defined on the basis of Gastropod and Chiton species associations, i.e., continental shelf (< 350 m), upper continental slope (> 350-2000 m) and lower continental slope (2000-3000 m). Bathymetry appears as the main factor modifying large-scale distribution of the fauna at a. In this scenario, species associations are determined by marine currents that clearly occur at a particular and well defined depth. No arrangement of species by geographic location was found in assemblages from the continental shelf and upper continental slope. Conclusions: We hypothesize that depth and marine currents are the main factor affecting the distribution of Gastropods and Chitons along the SW Atlantic between 200 and 3000 m depth.